A Phenomenological Investigation of Voluntary Exits from the Atmospheric Science Occupation - Kis, Amanda (My University, 2017)
Data available from several atmospheric science (including meteorology) degree programs suggest that a sizable number of degree-holding atmospheric scientists may work outside of the atmospheric science occupation. In cases of voluntary occupational turnover, it is likely that leavers and their former employers are paying substantial costs, and the reasons they left may reflect poorly on working conditions in the occupation. Unfortunately, the bulk of the existing literature on voluntary occupational turnover has several weaknesses and lacks context relevant to atmospheric science. The purpose of this study is to understand the roles played by occupational factors in voluntary exits from the atmospheric science occupation, in order to identify areas for improvement and thereby ensure the continued health of the occupation. A descriptive psychological phenomenological approach was used to uncover the general structure of the experience of voluntarily exiting the atmospheric science occupation, without relying on existing turnover variables and models. Semi-structured interviews were conducted with degree-holding atmospheric scientists who self-identified as having worked in the occupation for at least several months before voluntarily exiting it. This type of data collection was used to gather detailed qualitative data on the exit experience in order to better inform and motivate future data collection. The general structure of voluntarily exiting the atmospheric science occupation is that of filling needs that cannot be filled while staying in the occupation. Needs may center upon escaping an undesirable work environment, being able to do meaningful work, having security, and being physically present with loved ones. Issues related to imbalanced supply-and-demand and the nature of working in the occupation, such as lack of hiring or geographically-available jobs, prohibitive competition and educational or experience requirements, and lack of appealing jobs, may prevent working atmospheric scientists from filling their needs while staying in the occupation. These results are discussed in light of existing voluntary occupational turnover research and investigations of oversupply in the atmospheric science occupation. Additionally, the participants evaluated the avoidability of their exits and whether or not they would consider returning to the atmospheric science occupation in the future. Their answers to these questions give further insight into areas for improvement.
Keywords: Atmospheric Sciences Career Psychology